2022
DOI: 10.3389/fcimb.2022.804334
|View full text |Cite
|
Sign up to set email alerts
|

Limosilactobacillus (Lactobacillus) fermentum ALAL020, a Probiotic Candidate Bacterium, Produces a Cyclic Dipeptide That Suppresses the Periodontal Pathogens Porphyromonas gingivalis and Prevotella intermedia

Abstract: Periodontal disease develops as a result of oral microbiota in dysbiosis, followed by the growth of periodontal pathogens such as Porphyromonas gingivalis and Prevotella intermedia. In case of acute symptoms, antibacterial agents and disinfectants are administered, however the appearance of drug-resistant bacteria and allergies cause problems. In recent years, studies on the effects of probiotics have been conducted as an alternative therapy for periodontitis. However, the basic mechanism of the inhibitory eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In addition, some strains of bacteria isolated from the oral cavity have been produced commercially as probiotics, including Lactobacillus reuteri , Lactobacillus brevis and Streptococcus salivarius [ 25 , 43 ]. Kawai et al [ 44 ] suggested that Limosilactobacillus (Lactobacillus) fermentum ALAL020 may be a future probiotic candidate. This bacterium produces a cyclic dipeptide with antibacterial activity against Porphyromonas gingivalis and Prevotella intermedia [ 44 ].…”
Section: Microbiome In the Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some strains of bacteria isolated from the oral cavity have been produced commercially as probiotics, including Lactobacillus reuteri , Lactobacillus brevis and Streptococcus salivarius [ 25 , 43 ]. Kawai et al [ 44 ] suggested that Limosilactobacillus (Lactobacillus) fermentum ALAL020 may be a future probiotic candidate. This bacterium produces a cyclic dipeptide with antibacterial activity against Porphyromonas gingivalis and Prevotella intermedia [ 44 ].…”
Section: Microbiome In the Oral Healthmentioning
confidence: 99%
“…Kawai et al [ 44 ] suggested that Limosilactobacillus (Lactobacillus) fermentum ALAL020 may be a future probiotic candidate. This bacterium produces a cyclic dipeptide with antibacterial activity against Porphyromonas gingivalis and Prevotella intermedia [ 44 ]. Currently, the beneficial effects of synbiotics on health are of great interest to scientific research.…”
Section: Microbiome In the Oral Healthmentioning
confidence: 99%
“…38 In addition, a cyclic dipeptide synthesized by Lactobacillus fermentum ALAL020 was found to have a significant inhibitory effect on the growth and activity of P. gingivalis and Prevotella intermedia (P. intermedia). 39 Lactobacillus helveticus can enrich the expression of β-defensins in gingival epithelial cells, thereby inhibiting the inflammatory response induced by P. gingivalis. 40 The bipeptide bacteriocin PLNC8 αβ produced by Lactobacillus plantarum can also significantly inhibit P. gingivalis.…”
Section: Discussionmentioning
confidence: 99%
“…Nisin has also been found to be effective against A. actinomycetemcomitans, P. intermedia, P. gingivalis, F. nucleatum, and Treponema denticola 40 . Other bacteriocin-like peptides have also been found to be effective against periodontal pathobionts 41,42 .…”
Section: Discussionmentioning
confidence: 99%